Persistent and permanent splicing system - Fong , Wan Heng; Sarmin, Nor Haniza; Yusof, Yuhani (Faculty of Science, Universiti Teknologi Malaysia, 2009)
Splicing system was first introduced as a generative capacity of systems of restriction enzymes acting on an initial set of DNA molecules. Splicing language is the language resulting from a splicing system. There are many types of splicing languages. Among them are the persistent splicing language and permanent splicing language. These two types of splicing languages are not depended on the initial strings present in a splicing system. In this paper, some concepts and examples of persistent and permanent splicing system will be discussed. Furthermore, some examples are given to illustrate that not all splicing language resulting from a splicing system are persistent or permanent.